The Legislative Framework for Protecting Water Sources in Iraq (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2024)
Despite its great importance of water resources, they have not received much attention in legal thought. The interest in water resources t is the subject of legal philosophical discussions - both international and domestic. Signs of interest in it appeared in the last third of the 20th century and the first half of 21st century. Although the interest in water resources is intensified at the beginning of this century, internationally and the constitutionally. Furthermore, the interest in water sources from a natural standpoint is of great importance in Iraq, which has become threatened by drought and desertification, despite having two great rivers, the Tigris and Euphrates, whose sources are located outside Iraq, which is a large part of the problem in this area. Therefore, state and its various authorities has the responsibility of the to secure this right for its citizens.